2023
DOI: 10.3390/app13137487
|View full text |Cite
|
Sign up to set email alerts
|

Effective Quantization Evaluation Method of Functional Movement Screening with Improved Gaussian Mixture Model

Abstract: Background: Functional movement screening (FMS) allows for the rapid assessment of an individual’s physical activity level and the timely detection of sports injury risk. However, traditional functional movement screening often requires on-site assessment by experts, which is time-consuming and prone to subjective bias. Therefore, the study of automated functional movement screening has become increasingly important. Methods: In this study, we propose an automated assessment method for FMS based on an improved… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Unless otherwise specified, the AM used in this work defaults to Simple-AM. This paper conducts comparative experiments on a single action between the FMS dataset and the improved Gaussian mixture model (GMM) [1]. It also conducts comparative experiments with the advanced methods of video action quality evaluation in this paper, verifying that the proposed method can effectively predict the FMS dataset and achieve excellent results.…”
Section: Analysis Of Prediction Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…Unless otherwise specified, the AM used in this work defaults to Simple-AM. This paper conducts comparative experiments on a single action between the FMS dataset and the improved Gaussian mixture model (GMM) [1]. It also conducts comparative experiments with the advanced methods of video action quality evaluation in this paper, verifying that the proposed method can effectively predict the FMS dataset and achieve excellent results.…”
Section: Analysis Of Prediction Resultsmentioning
confidence: 79%
“…In recent years, researchers have introduced a multitude of methods to automate the evaluation of FMS. Hong et al [1] utilized a Gaussian mixture model and explored various machine learning techniques, such as naïve Bayes, AdaBoost, M1, and traditional Gaussian models, to address this issue. However, these methods face difficulties in modeling complex human motion patterns, which can lead to a decrease in accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…However, it increases the computational complexity of the network, especially in situations where a large quantity of computational resources are needed. Hong et al [7] proposed an automatic FMS evaluation method based on an improved Gaussian mixture model (GMM). The authors trained the GMM using feature data with various scores.…”
Section: Introductionmentioning
confidence: 99%
“…The study combines the feature fusion methods of optical flow and RGB stream to address [5,6] the challenge of fusing RGB with dual streams in the case of an insufficient dataset scale and diversity, which makes training data features become more specific. According to [7,8], the deficiencies of poor training outcomes on unknown training sets, and unsatisfactory feature extraction, this study aimed to enhance the robustness of training results by achieving RGB and dual-stream fusion using some fusion methods from feature fusion. The core contributions of this paper can be summarized in the following three aspects, which involve innovation in data fusion techniques and its significant effects on performance improvement:…”
Section: Introductionmentioning
confidence: 99%
“…These methods require less data and offer interpretability through manual feature extraction. Moreover, Hong et al [13] demonstrated the feasibility of using depth cameras in FMS assessment by collecting a dataset using Azure Kinect depth sensors. They improved the accuracy of FMS assessment by forming a robust classifier that combines three Gaussian mixture models, each trained on datasets with different scores.…”
Section: Introductionmentioning
confidence: 99%